Drags: A compositional algebraic framework for graph rewriting - Dershowitz, Nachum; Jouannaud, Jean-Pierre (Theoretical computer science, 2019)
We are interested in a natural generalization of term-rewriting techniques to what we call drags, viz. finite, directed, ordered, rooted multigraphs, each vertex of which is labeled by a function symbol. To this end, we develop a rich algebra of drags that generalizes the familiar term algebra and its associated rewriting capabilities. Viewing graphs as terms provides an initial building block for rewriting with such graphs, one that should impact the many areas where computations take place on graphs.